ETHNOSCIENCE INTEGRATION BASED ON LOCAL WISDOM OF KUDUS IN SCIENCE LEARNING TO IMPROVE STUDENTS' SCIENCE LITERACY - Zulfa, Laili Shofiyatuz; Zulfa, Illayya; Sa’diyah, Anggun Zahrotus; Dzofir, Mohammad (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Science learning in Islamic schools requires contextual and meaningful approaches to enhance students' scientific literacy. One relevant approach is ethnoscience, which integrates scientific concepts with local wisdom. This study aims to examine the ethnoscience values ​​contained in the local wisdom of Menara Kudus and their relevance for integration into science learning in Islamic schools to improve students' scientific literacy. This research employed a descriptive qualitative approach using observation, in-depth interviews with cultural informants, and documentation as data collection techniques. The results indicate that Menara Kudus contains various ethnoscience values ​​encompassing physical, chemical, environmental, and socio-cultural aspects. Physical and chemical aspects are reflected in the use of red brick materials, traditional construction techniques without modern cement, and principles of force, balance, and structural stability. Environmental aspects are evident in the building's adaptation to the tropical climate, while socio-cultural aspects are represented by the value of tolerance taught by Sunan Kudus. These findings demonstrate that Menara Kudus has significant potential as a contextual and holistic ethnoscience-based science learning resource. Integrating these values ​​into science learning in Islamic schools is expected to enhance students' scientific literacy while simultaneously strengthening character education.